Effect of Landa’s Model on the Development of Creative Thinking of Primary School Students in the Group of Family and Technical and Vocational Education - Jumaah, Ali Kadhim; Sejzi, Abbas Abdoli (Indian Journal of Information Sources and Services, 2025)
Teaching creativity skills to learners is one of the most important goals of those involved in education. This research aims to evaluate the effect of Landa’s model on the development of creative thinking of primary school students in the family and technical and vocational education groups. The research uses the method of quasi-experimental designs "pre-test-post-test with control group and matched". The population of 1050 male students of elementary schools in Baghdad city – Iraq is considered. The sample size of two classes with 30- students was selected by random cluster sampling from among 21 boys’ classrooms in Baghdad and they were assigned into two groups: Landa and simple method. Multivariate covariance analysis is performed using SPSS statistical software to explain the research hypotheses. The results of the study indicate the existence of a significant difference in each of the dimensions of creative thinking, including innovation, expansion, flexibility and fluidity, between the two experimental groups (using the Landa method) and the control group (using the traditional method). In other words, the use of Landa’s method has ascertained a significant effect on students’ ability to think creatively compared to the use of the traditional method. The results of the first hypothesis show that the students who were taught by the Landa method, compared to their peers who did not experience this method, have a significant difference in the ability to think creatively in social studies. In particular, teaching social studies using the Landa method has been significantly more effective than the traditional method in strengthening students’ creative thinking .